Possibilities of Facebook in university teaching from a case study - María Cristina López de la Madrid; Katiuzka Flores Guerrero; Adolfo Espinoza de los Monteros Cárdenas; Diana Rojo Morales (Universidad de Guadalajara, 2017)
This article presents a descriptive study whose objective was to identify the possibilities of the social network Facebook in the field of teaching. For this purpose, a closed reagent survey was designed and applied to a sample of 142 higher education teachers. We also worked on an open question from which we generated categories of analysis that complemented the quantitative results represented by frequencies in percentages. Some of the most significant findings refer the high frequency of use of Facebook (daily), and the mastery between medium and high that has the majority of teachers (90.92%) in the use of this social network. We find a great variety of uses of Facebook, in the teaching process and in the rest of the activities of teachers, which may be of special interest to those teachers who want to implement this social network to their practice. We identified some negative factors such as lack of structure and excessive visual noise. We conclude that, with a proper direction and design, Facebook can promote dynamic and attractive learning environments for higher education students.